FULMINANT MYOCARDITIS IN THE DOCTOR'S PRACTICE - M. R. Bakhchoyan; E. D. Kosmacheva; A. A. Slavinsky; A. A. Skopets; L. M. Chuprinenko; V. A. Porhanov (Кубанский научный медицинский вестник, 2016)
The article is devoted to the peculiarities of diagnosis and treatment of fulminant myocarditis in young women. This clinical case confirms that etiopathogenetic complex therapy was implemented in a specialized Cardiac Intensive Care Department in conjunction with the necessary diagnostic and invasive procedures that are the optimal options for the diagnosis and treatment of patients with acute myocarditis.